Geographic patterns in the behavior, seasonality, and habitat use of humpback whales within the Kitimat Fjord System. - Janie Wray (457395); Eric Keen (11014169); Éadin N. O’Mahony (11014172) (2021)
In each pane, the black line indicates the frequency of each variable of interest, pooled into bins of swimming distance from the interior of the fjord system (bin size = 10km, 0–100 km. Blue shaded area represents the frequency expected by random chance, determined via randomization (1,000 iterations; blue line = median; shading = 95% confidence interval, determined using 0.025 and 0.975 quantiles).